READ ALOUD: A LITERACY ACTIVITY IN ELEMENTARY SCHOOL - Nunuy Nurkaeti; Sani Aryanto; Yosi Gumala (PrimaryEdu : Journal of Primary Education, 2019)
Reading literacy is the main key on develop knowledge. Reading literacy in elementary schools was developed through the implementation of the school literacy movement. The literacy activities are carried out as evidence of the implementation of the school literacy movement. This study aims to describe the implementation of reading literacy activity and read aloud in elementary schools. The research method used was descriptive qualitative through data collection based on a questionnaire and documentation study at ten elementary schools in Majalengka. The results show that literacy activities have been implemented in primary schools, although they have not been routinely carried out. Reading literacy methods used include read aloud, review, alphabetical methods, and reading comprehension. There are schools that have used read aloud as an effort to increase the reading literacy of elementary school students. Generally teachers in schools do not yet know the read aloud and its implementation. Training is needed for teachers to developing literacy activities in primary schools, so that could optimizing literacy activities through the use of various reading strategies.